Isolated Cardiac Sarcoidosis with High-Grade Heart Block: Utilization of New Diagnostic Guidelines. (29th July 2021) - Petersen, Matthew R.; Perry, Christopher; Nickels, Rachel
Abstract : Cardiac sarcoidosis can present with heart failure and conduction disease. This is a case of a 58-year-old male who presented for dyspnea, edema, and varying degrees of heart block. Using new updated diagnostic guidelines and multimodal cardiac imaging, he was diagnosed with isolated cardiac sarcoidosis.